What is Islam? : the importance of being Islamic - Ahmed, Shahab, 1966-2015 (Princeton ; Oxford : Princeton University Press, 2016)
"A book that is certain to provoke debate and significantly alter our understanding of Islam, [this work] reveals how Muslims have historically conceived of and lived with Islam as norms and truths that are at once contradictory yet coherent"--Front jacket flap
"What is Islam? How do we grasp a human and historical phenomenon characterized by such variety and contradiction? What is "Islamic" about Islamic philosophy or Islamic art? Should we speak of Islam or of islams? Should we distinguish the Islamic (the religious) from the Islamicate (the cultural)? Or should we abandon "Islamic" altogether as an analytical term? In What Is Islam?, Shahab Ahmed presents a bold new conceptualization of Islam that challenges dominant understandings grounded in the categories of "religion" and "culture" or those that privilege law and scripture. He argues that these modes of thinking obstruct us from understanding Islam, distorting it, diminishing it, and rendering it incoherent. What Is Islam? formulates a new conceptual language for analyzing Islam. It presents a new paradigm of how Muslims have historically understood divine revelation--one that enables us to understand how and why Muslims through history have embraced values such as exploration, ambiguity, aestheticization, polyvalence, and relativism, as well as practices such as figural art, music, and even wine drinking as Islamic. It also puts forward a new understanding of the historical constitution of Islamic law and its relationship to philosophical ethics and political theory. A book that is certain to provoke debate and significantly alter our understanding of Islam, What Is Islam? reveals how Muslims have historically conceived of and lived with Islam as norms and truths that are at once contradictory yet coherent."--Publisher's description
Part one. Questions. What is Islam? ; Chapter 1. Six Questions about Islam -- Part two. Conceptualizations. Chapter 2. Islam as Law, islams-not-Islam, Islamic and Islamicate, Religion and Culture, Culture and Civilization ; Chapter 3. Religion and Secular, Sacred and Profane, Theocentric and Anthropocentric, Total Social Fact, Family Resemblance ; Chapter 4. Culture, Meaning, Symbol System, Core and Nucleus, Whatever-Muslims-Say-It-Is, Discursive Tradition, Orthodoxy, Process -- Part three. Re-Conceptualizations. Chapter 5. Hermeneutical Engagement, Pre-Text, Text, and Con-Text, Meaning-Making for the Self, Spatiality of Revelation, Hierarchy, Exteriority-Interiority, Public and Private, Language and Vocabulary, Ambivalence and Ambiguity, Metaphor and Paradox ; Chapter 6. Applications and Implications : Coherent Contradiction, Exploration, Diffusion, Form and Meaning, Modern ; The Importance of Being Islamic
Includes bibliographical references and index
Jacket image © Heritage Auctions
English.
Keywords: Islam